Formal definition of the Lower Jurassic McCoy Brook Formation, Fundy Rift Basin, eastern Canada - Tanner, Lawrence (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
The name McCoy Brook Formation, presently in informal use, is formally proposed to designate outcrops of Lower Jurassic (Hettangian-Pliensbachian) strata overlying the North Mountain Basalt in the structural Minas Subbasin of the Fundy Rift Basin. It is also proposed that this designation be extended to include stratigraphically equivalent strata beneath the Bay of Fundy throughout the entire Fundy Rift Basin. It is further recommended that use of the name Scots Bay Formation, the current designation for post-basalt Jurassic sediments outcropping on the south side of the Minas Subbasin, be discontinued. The name Scots Bay Member of the McCoy Brook Formation is used here to designate distinctive lacustrine strata at the base of the McCoy Brook Formation outcropping on both sides of the Minas Subbasin.